2015
DOI: 10.1364/oe.23.017120
|View full text |Cite
|
Sign up to set email alerts
|

SDM transmission of real-time 10GbE traffic using commercial SFP + transceivers over 05km elliptical-core few-mode fiber

Abstract: We experimentally demonstrate the first few-mode space division multiplexed (SDM) transmission of real-time 10Gb/s Ethernet (10GbE) traffic using commercial small form-factor pluggable SFP + transceivers without coherent detection or multiple input multiple output digital signal processing (MIMO-DSP) over 0.5km elliptical-core few-mode-fiber, achieving <-26dB crosstalk between LP(11e) and LP(11o) modes at 1.3μm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
53
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(54 citation statements)
references
References 6 publications
0
53
0
1
Order By: Relevance
“…When considering high capacity, short-reach data-center applications however, where both cost and power consumption need to be kept as low as possible, the use of MIMO-less direct detection is imperative, and this imposes stringent requirements on the tolerable cross-talk levels among the transmitted modes. Recently, the use of elliptical (multi-) core FMF has been proposed as a means to guarantee negligible mode coupling even between modes of the LP 11 mode group that are normally degenerate [2][3][4][5]. Notably, MIMO-less SDM transmission using three-spatial-modes (LP 01 , LP 11a and LP 11b ) at 1.3 m and two-spatial-modes (LP 01 and LP 11a ) at 1.5 m was demonstrated in a (sub) km-long FMF with a core-ellipticity of about 40% [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering high capacity, short-reach data-center applications however, where both cost and power consumption need to be kept as low as possible, the use of MIMO-less direct detection is imperative, and this imposes stringent requirements on the tolerable cross-talk levels among the transmitted modes. Recently, the use of elliptical (multi-) core FMF has been proposed as a means to guarantee negligible mode coupling even between modes of the LP 11 mode group that are normally degenerate [2][3][4][5]. Notably, MIMO-less SDM transmission using three-spatial-modes (LP 01 , LP 11a and LP 11b ) at 1.3 m and two-spatial-modes (LP 01 and LP 11a ) at 1.5 m was demonstrated in a (sub) km-long FMF with a core-ellipticity of about 40% [2].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of elliptical (multi-) core FMF has been proposed as a means to guarantee negligible mode coupling even between modes of the LP 11 mode group that are normally degenerate [2][3][4][5]. Notably, MIMO-less SDM transmission using three-spatial-modes (LP 01 , LP 11a and LP 11b ) at 1.3 m and two-spatial-modes (LP 01 and LP 11a ) at 1.5 m was demonstrated in a (sub) km-long FMF with a core-ellipticity of about 40% [2]. The same authors also demonstrated 1.2 Tbit/s wavelength division multiplexing (WDM) + SDM transmission at 1.5 m using a four-core FMF with each core having an ellipticity of about 11% and supporting two spatial mode groups.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial-Division Multiplexing (SDM) or Mode-Division Multiplexing (MDM) are promising techniques to increase the capacity of fiber optic communication networks [5], [6]. MDM increases the fiber capacity by means of the parallel transmission of different information through the available spatial modes at a specific wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…OAM modes and other modes are used for optical communication [5][6][7][8][9][10][11][12][13] . Like other facets of light, OAM modes can be used for remote sensing.…”
mentioning
confidence: 99%